(untitled) (Acta Scientiarum. Animal Sciences, 2025)
Over the last few decades, the Indonesian government has designed a partnership model for the farming system called an inti-plasma model. An inti or a core was a large private company, while the plasmas were smallholders that collaborated with the core. In the subsector of animal husbandry, the animal housing system has been considered the main regulation to achieve a contract between the core and plasmas. This study aimed to evaluate the performance comparison of broiler chickens kept in the closed house (CH) versus those kept in the stage slatted-floor open-sided house (OH) at broiler farms in Desa Simpang Jambe, Indonesia, in partnership with Charoen Pokphan Jaya Farm. This study was conducted in a completely randomized design (CRD) with two treatments and ten replications. The treatments were broilers reared in CH, and those in the OH. Each replication was an experimental unit with 4,800 birds pen-1 in the CH and 600 birds pen-1 in the OH. Twenty birds were randomly sampled from each pen for body weight (BW) and feed intake (FI), resulting in 200 sampling birds from each house. Data were analyzed using a t-test analysis. The results of this study showed that during the starter period, BW, body weight gain, feed intake, mortality, and depletion were significantly better at p < 0.05 and p < 0.01 in the OH than in the CH, but feed conversion ratio was not significantly different at p > 0.05 between both houses. However, during the grower/finisher and overall periods, all performance parameters were significantly different (p < 0.01) by house type. In conclusion, producing broilers at 4 or 5 weeks of marketed ages in the closed house performed better performance index than those in the stage slatted-floor open-sided house.